Succession and controlling factors of phytoplankton assemblages during a period with recurrent outbreaks of Phaeocystis globosa blooms in Qinzhou Bay, China - Qin, Xianling; Chen, Xianyun; Chen, Changping; Sun, Lin; Su, Xinying; Liang, Junrong; Chen, Bo; Gao, Yahui (Frontiers in Marine Science, 2023)
Qinzhou Bay is a tropical semiclosed bay with the highest phytoplankton diversity and a high frequency of harmful algal blooms (HABs) in the Guangxi coastal area, located north of the Beibu Gulf. Phaeocystis globosa is a typical HAB species in the Guangxi coastal area, and blooms mainly occur in autumn and winter. The causes of these blooms and the succession of phytoplankton assemblages related to the blooms are complicated and not fully understood. Therefore, a continuous survey was conducted monthly from October 2018 to March 2019 to study the succession of the phytoplankton community in Qinzhou Bay and its relationship with environmental variables in this area. The results revealed that the dynamics of the phytoplankton assemblages varied significantly with time, and P. globosa was the most frequent dominant species in five of these voyages, with the highest cell density of 3.79 ± 1.34 × 106 cells/L in January. Chaetoceros species had a high density and were a dominant species associated with P. globosa in the early stage, while they were replaced by Guinardia striata when the density of P. globosa increased rapidly in January, and the abundance of dinoflagellates increased after the decline in P. globosa. The diversity index indicated that the community structure was more stable from October to December, while the sharp increase in P. globosa in January caused a decline in phytoplankton diversity. The redundancy analysis (RDA) results revealed that the phytoplankton community structure and its variation were mainly affected by hydrological and chemical factors, including DIN/DIP, temperature, DSi, DIP and DSi/DIP. Furthermore, we inferred that phosphorus (P) was the key factor limiting the colony formation of P. globosa, and P limitation prevented the outbreak of blooms. This research may provide more insight into the mechanisms driving and prevention of P. globosa blooms.